Chinese Literacy Learning in an Immersion Program - Lü, Chan (Springer International Publishing : Imprint: Palgrave Macmillan, 2019)
This book examines one-way foreign language immersion education in the United States. It provides a clear and rich description of a Chinese (Mandarin) immersion program, its curriculum, instructional materials, assessment activities, parental involvement and student outcomes. The author analyses two studies that document the development of the students' reading skills in English and Chinese, and the progress of their vocabulary knowledge, lexical inference, and reading comprehension in Chinese. In addition, this book contextualizes the program in its eco-system, including its neighbourhood, school, and the school district, and discusses the importance of school leadership, parental involvement, neighbourhood support and language acquisition planning in making an innovative school program successful. Its concluding chapters offer recommendations for program- and classroom-level practices and suggest pathways for future research on biliteracy learning in Chinese one-way immersion programs. This book will appeal in particular to students and scholars of applied linguistics, second language acquisition and language education. Chan Lü is Assistant Professor of Chinese Language and Linguistics in Department of Asian Languages and Literature at the University of Washington, USA.